Regional Subsurface Dolomitization: Models and Constraints - Morrow, D. (Geoscience Canada, 1998)
The "topographic recharge" and "tectonic compaction" models for subsurface fluid flow may have been over-applied to the question of the origin of regional hydrothermal dolomite bodies. These have been attractive models to explain hydrothermal dolomitization because of their obvious applicabilty to the present day hydrology of continental interiors. However, recent modelling studies indicate that topographic recharge does not predict the uniform regional trends of dolomite precipitational temperatures observed in hydrothermal dolomites, and that tectonic compaction requires an unreasonable degree of fluid focusing to achieve precipitational temperatures equal to observed dolomite fluid inclusion homogenization temperatures. Topographic recharge also has the limitation of flushing solutes out of the system, rendering it incapable of further dolomitization. In addition, both topographic recharge and tectonic compaction are unlikely flow mechanisms to explain the origin of extensive open space dolomite cement because of their limited supply of solute. Thermal convection, on the other hand, can support long-lived flow systems that are capable of recycling subsurface solutions many times through the rock mass. This enhances the opportunity for open space dolomite cementation. Because thermal convection can occur in confined aquifers beneath the sea bed, seawater-derived solutions may be continually added to the convection system. Added seawater would enhance the dolomitization potential of the convection system. The documentation of crustal scale convection systems within subaerially exposed orogenic belts and the outcrop evidence of both upward and downward extending bodies of hydrothermal dolomite adds credence to the hypothesis that thermally driven convective flow occurred within ancient platform carbonates, and may have induced regional hydrothermal dolomitization. Résumé On a peut-être abusé des modèles explicatifs courants du flux des fluides souterrains dit de recharge topographique, et de compaction tectonique, en les utilisant pour expliquer l’existence de grands ensembles régionaux de dolomies hydrothermales. Sans doute à cause de leur grande utilité en hydrologie continentale on aura présumé que ces deux modèles pouvaient s’appliquer au cas de la dolomitisation hydrothermale régionale. Cependant, des modélisations récentes indiquent que la recharge topographique ne permet pas d’expliquer l’uniformité régionale de la température de précipitation observée dans les dolomies hydrothermales, et d’autre part, la compaction tectonique présuppose l’existence d’un phénomène de convergence des fluides injustifiable permettant d’arriver aux températures d’homogénéisation observées dans les inclusions fluides des dolomies. L’évacuation des produits dissous à l’extérieur du système et qui caractérise le modèle de la recharge topographique, ne permet pas d’expliquer l’existence de phases répétées de dolomitisation. De plus, ni la recharge topographique, ni la compaction tectonique ne sont des modèles de flux capable d’expliquer l’existence de volumes importants de ciments vacuolaires de dolomie. En contrepartie, le modèle de convection thermale peut très bien expliquer l’existence de systèmes d’écoulement à durée de vie suffisamment longue pour permettre le passage de plusieurs cycles de solutions aqueuses souterraines à travers les masses rocheuses encaissantes. Cette particularité de la convection thermale augmente d’autant les possibilités de formation de ciments vacuolaires de dolomie. N’étant pas confinée au domaine continental, la convection thermale peut agir au sein d’aquifères captifs sous-marins et permettre l’apport continu d’eau marine au système de convection, augmentant ainsi les possibilités de dolomitisation. L’existence documentée de systèmes de convection dans des écailles tectoniques crustales au sein de bandes orogéniques subaériennes, et d’affleurements d’importantes zones de dolomies hydrothermales, autant au-dessus qu’en-dessous du niveau topographique, renforcent l’hypothèse de la présence d’un flux par convection thermique au sein d’anciennes plate-formes de carbonates, phénomène qui pourrait avoir provoqué une dolomitisation hydrothermale régionale.